2015
DOI: 10.1007/s11095-014-1613-y
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Chitosan on the Oral Bioavailability of Acyclovir—a Comparative Bioavailability Study in Humans

Abstract: PurposeThe effects of chitosan hydrochloride on the oral absorption of acyclovir in humans were studied to confirm the absorption enhancing effects reported for in vitro and rat studies, respectively.MethodsA controlled, open-label, randomized, 3-phase study was conducted in 12 healthy human volunteers. Zovirax 200 mg dispersible tablets co-administered with doses of 400 and 1000 mg chitosan HCl were compared with Zovirax only.ResultsThe expected increased absorption of acyclovir was not observed. On the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 42 publications
(38 reference statements)
0
29
0
Order By: Relevance
“…Acyclovir (ACV), an antiviral drug, is a purine nucleoside analog, used against viruses of the herpes group (Nair et al, 2014). Currently it is available in the market as topical ointment, as capsules in the strength of 200 mg and as tablets in strength of 200 mg, 400 mg and 800 mg (Kubbinga et al, 2015). The mean plasma half-life of the drug is 3 h (Naik and Raval, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Acyclovir (ACV), an antiviral drug, is a purine nucleoside analog, used against viruses of the herpes group (Nair et al, 2014). Currently it is available in the market as topical ointment, as capsules in the strength of 200 mg and as tablets in strength of 200 mg, 400 mg and 800 mg (Kubbinga et al, 2015). The mean plasma half-life of the drug is 3 h (Naik and Raval, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another drawback to native chitosan is the gelling properties at concentrations as low as 1.5% [410], which impacts optimal release and presentation of peptide and PE at the intestinal epithelium. An assessment of chitosan acetate as a tablet binder showed that inclusion of low concentrations (1, 2, or 3 % w/w) prolonged dissolution of theophyline from tablets to beyond 3 h, which contrasted to dissolution from tablets [418]. It seems that oral delivery of chitosan in fluidic dispersions in man do not mirror the enhancement data observed in pre-clinical delivery models.…”
Section: Case 16: Chitosan and Its Derivativesmentioning
confidence: 99%
“…Absorption enhancers are functional excipients to improve the absorption of active drug. For oral delivery of heparins, absorption enhancers refer to an agent whose function is to increase intestinal epithelial membrane permeability, sometimes they are also specifically called permeability enhancers [76] .These include a series of natural, synthetic and semi-synthetic substances, such as surfactants [77] , EDTA [78] , chitosan and chitosan derivatives [79] , [80] , [81] , [82] . The commonly used absorption enhancers for heparins are shown in Table 2 [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] .…”
Section: Strategies For Oral Delivery Of Heparinsmentioning
confidence: 99%
“… Heparins Enhancer Model Enhancement ratio Ref. UFH Sodium N-[8-(2-hydroxybenzoyl)amino] (SNAC) In vivo pharmacokinetic study in rats SNAC significantly increased anti-Xa levels, whereas UFH alone caused no significant change in anti-Xa levels [75 , 76] LMWH Sodium N-[10-(2-hydroxybenzoyl) (SNAD) In vivo pharmacodynamic study in a porcine model of deep venous thrombosis AntifactorXa levelswere significantly elevated in the LMWH/SNAD group versus baseline [77] LMWH Chitosan oligomers In-situ closed loop method in rats Papp in small intestine: 1.6–9.2 [78] Papp in large intestine: 3.7–13.2 LMWH Thiolated chitosan Oral administration in rats Absolute bioavailability: ∼5.79 [79] LMWH Methylated chitosan In vivo pharmacokinetic study in rats ∼ 2.4 [80] LMWH PCP-Cys/GSH Ex vivo using type chambers method and in vivo pharmacokinetic study in rats Papp: 2.2 [81] Absolute bioavailability: at least ∼8.7 LMWH L-arginine Ex vivo using type chambers method and in vivo absorption study in rats Papp: 2.1–3.0 [82] Absolute bioavailability: at least 1.6 LMWH N-sulfonato-N,O-carboxymethylchitosan In vitro Caco-2 cells and in vivo duodenum administration Papp: at least 1.4 Absolute bioavailability: at least 16 [83] LMWH Polycationic lipophilic-core dendrons …”
Section: Strategies For Oral Delivery Of Heparinsmentioning
confidence: 99%